Preparation and application of a D–A conjugated electrochromic flexible electrode with side chain carbazole active groups in supercapacitors. (23rd September 2021) - Wang, Pengna; Sun, Ying; Li, Jie; Kang, Weiwei; Zhu, Guanqun; Zhang, Huijun; Zhang, Xueqin; Yang, Hong; Lin, Bao-Ping
Abstract : Electrochromic power storage devices (ESCs) integrate energy storage and electrochromic behaviour into a single full cell that can enable the visualization of the energy status by the naked eye. Abstract : Electrochromic power storage devices (ESCs) integrate energy storage and electrochromic behaviour into a single full cell that can enable the visualization of the energy status by the naked eye. One challenge for achieving practical applications is the development of intelligent and portable all-organic electrochromic power storage devices. Donor–acceptor (D–A) polymers have been widely studied for their tunable electronic properties. However, studies of polymers with optoelectrochemical, electrochromic and electrochemical performance substituted with different carbazole groups have drawn little attention. Herein, we designed and synthesized four polymers with carbazole side chains. The polymer solutions can be simply processed into thin films. Meanwhile, they exhibit an obvious and reversible colour transition between red (uncharged state) and dark blue (charged state), with an optical contrast of 37.35% and a colouring efficiency of 241.40 cm 2 C −1 at a wavelength of 661 nm. The electrochromic components of PI-2 and PI-3 were assembled and proved to be able to change colour in the bending state. Hence, the energy storage level of the ESCs is directly related to their colour and can be determined by the naked eye, which means that they can be incorporated with other energy cells to visually display their energy status. PI-3 was assembled into a flexible supercapacitor that lighted up a 1.5 V light-emitting diode. Finally, the results present significant potential of PI-3 electrodes for efficient energy storage and electrochromic properties with stable transmittance changes, demonstrating their potential as smart wearable energy storage devices. This work can provide a platform for developing smart and portable power storage devices with enhanced energy densities.